Codes of Professional Conduct and Ethics Education for Future Teachers - Maxwell, Bruce (Philosophical Inquiry in Education, 2017)
This paper argues that the way future teachers are being initiated into the ethical dimensions of their future profession is largely out of step with the movement to professionalize teaching. After recalling the role that codes of professional conduct play in the ecology of professional self-regulation, and arguing that familiarizing students with their local code of ethics should be considered is the bare minimum of an adequate ethics education for professionals, the paper presents research findings indicating that education students are not leaving colleges and universities with a clear understanding of what is expected of them by society, their peers and the profession. The paper concludes with three suggestions about how to begin bringing ethics education for teachers more into line with teaching’s aspiration to professional status.